China’s Tortuous Path Toward Ending Torture in Criminal Investigations - Belkin, Ira (Columbia Journal of Asian Law, 2011)
On May 21, 2010, Chief Judge Zhang Liyong of the Henan Provincial High Court left his office in the provincial capital of Zhengzhou and travelled to a remote peasant village. There, in front of national television cameras, he bowed deeply three times and personally offered his apologies to Zhao Zuohai, a poor farmer, for his unjust murder conviction.’ Thus, a “month of reflection” in all of the “judicial organs”-the courts, the prosecutors’ offices and the police of Henan Province-came to a close. This rare public display of contrition by Chinese officialdom was occasioned by this embarrassing case of the Chinese justice system convicting an innocent man of a murder that had never occurred. There was no gainsaying the wrongfulness of the conviction and the innocence of Zhao Zuohai. This was not a case of a guilty party getting off on a technicality. After serving eleven years in prison, Zhao Zuohai was exonerated by the most persuasive evidence possible: after more than a decade’s absence, the alleged murder victim, Zhao Zhanshang (no relation), returned to their home village still very much alive to claim social welfare benefits. Village officials were shocked to see Zhao Zhanshang “return from the dead.”